The health professionals’ perspectives of support needs of adult head and neck cancer survivors and their families: a Delphi study - Breen, Lauren; O'Connor, Moira; Calder, Samuel; Tai, Vivian; Cartwright, Jade; Beilby, Janet (Springer, 2017)
Purpose: The aim was to identify the views of Australian and New Zealand health professionals regarding the support needs of people with head and neck cancer (HNC) and their families and current gaps in service delivery. Methods: A modified Delphi process assessed support needs of people with HNC following acute medical management. A systematic review of the literature was used to develop items relevant to seven key concepts underpinning the psychological experience of living with HNC. A panel of 105 health professionals was invited to participate in two questionnaire rounds. Results: Of the potential panellists, 50 (48%) completed round 1, and of these, 39 (78%) completed round 2. Following two rounds, there was consensus agreement on the concepts uncertainty and waiting, disruption to daily life and fear of recurrence. The concepts the diminished self, making sense of and managing the experience, sharing the burden and finding a path did not achieve consensus. There were no differences in responses according to gender, organization type or location. Medical professionals had significantly higher agreement for the concept uncertainty and waiting compared to allied health professionals, and professionals with five years’ or more experience had significantly higher agreement than those with less experience. Conclusions: Health professionals agreed that many psychosocial support needs of HNC survivors and families are not being met and that they experience difficulties in meeting these needs. Findings may inform evidence-based treatment programs for HNC survivors and their families to promote psychological resilience and quality of life in this vulnerable population.